Semantic intrusion errors are associated with plasma Ptau-181 among persons with amnestic mild cognitive impairment who are amyloid positive - Curiel Cid, Rosie E.; Ortega, Alexandra; Crocco, Elizabeth A.; Hincapie, Diana; McFarland, Karen N.; Duara, Ranjan; Vaillancourt, David; DeKosky, Steven T.; Smith, Glenn; Sfakianaki, Efrosyni; Rosselli, Monica; Barker, Warren W.; et al. (Frontiers in Neurology, 2023)
Semantic intrusion errors (SI) have distinguished between those with amnestic Mild Cognitive Impairment (aMCI) who are amyloid positive (A+) versus negative (A-) on positron emission tomography (PET). This study examines the association between SI and plasma -based biomarkers. One hundred and twenty-eight participants received SiMoA derived measures of plasma pTau-181, ratio of two amyloid-β peptide fragments (Aβ42/Aβ40), Neurofilament Light protein (NfL), Glial Fibrillary Acidic Protein (GFAP), ApoE genotyping, and amyloid PET imaging. The aMCI A+ (n=42) group had a higher percentage of ApoE ɛ4 carriers, and greater levels of pTau-181 and SI, than Cognitively Unimpaired (CU) A-participants (n=25). CU controls did not differ from aMCI A-(n=61) on plasma biomarkers or ApoE genotype. Logistic regression indicated that ApoE ɛ4 positivity, pTau-181, and SI were independent differentiating predictors (Correct classification=82.0%; Sensitivity=71.4%; Specificity=90.2%) in identifying A+ from A-aMCI cases. A combination of plasma biomarkers, ApoE positivity and SI had high specificity in identifying A+ from A-aMCI cases.